2022
DOI: 10.1080/10872981.2022.2044635
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the World Health Organization Well-Being Index (WHO-5) among medical educators in Hong Kong: a confirmatory factor analysis

Abstract: Background The COVID-19 pandemic has exacerbated the pre-existing global crisis of physician burnout. Physician and particularly medical educator well-being, has come into focus as educators can influence their own and learners’ well-being. Measuring this construct is one important step towards promoting well-being in the work and learning environments. The 5-item World Health Organization Well-Being Index (WHO-5) has been validated in different populations worldwide for assessing well-being. Yet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…These combined findings emphasize that nurses from Norway reported better well-being than those in Spain and Chile during the pandemic. These results appear consistent with studies reporting that the WHO-5 Well-Being Index can differentiate between populations [ 31 , 43 , 45 ]. However, further research, using several measurement points, is needed to investigate whether the nurses’ mental well-being changes over time and whether the WHO-5 Well-Being Index can capture these changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These combined findings emphasize that nurses from Norway reported better well-being than those in Spain and Chile during the pandemic. These results appear consistent with studies reporting that the WHO-5 Well-Being Index can differentiate between populations [ 31 , 43 , 45 ]. However, further research, using several measurement points, is needed to investigate whether the nurses’ mental well-being changes over time and whether the WHO-5 Well-Being Index can capture these changes.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to previous studies showing low Cronbach’s alpha [ 42 ], the WHO-5 Well-Being Index showed high internal consistency in the three countries, with Cronbach’s alpha varying from 0.810 to 0.903 (Norway to Chile). These findings are within the range of Cronbach’s alpha reported in validation studies among medical educators in Hong Kong [ 43 ], outpatients with epilepsy in Denmark [ 44 ], adults living with epilepsy and HIV in Kenya [ 45 ] and among Chinese university students [ 46 ].…”
Section: Discussionsupporting
confidence: 72%
“…In a 2015 systematic review, Topp et al found that the tool had high clinimetric validity and could be used effectively as a non-invasive, subjective measure of well-being [17]. Previous research has also reported structural and construct criterion validity using the WHO-5 Index in numerous countries and populations [18,19]. Cronbach alphas ranged from 0.81-0.90 in a study of medical educators concluding the instrument to be a psychometrically sound tool for measuring well-being [18].…”
Section: Measuring Burnout and Well-beingmentioning
confidence: 99%
“…Previous research has also reported structural and construct criterion validity using the WHO-5 Index in numerous countries and populations [18,19]. Cronbach alphas ranged from 0.81-0.90 in a study of medical educators concluding the instrument to be a psychometrically sound tool for measuring well-being [18]. However, in a study of adolescent mental well-being spanning 15 countries, the elimination of the first item on the questionnaire ("I have felt cheerful and in good spirits") resulted in better psychometric properties in that population [20].…”
Section: Measuring Burnout and Well-beingmentioning
confidence: 99%
“…Researchers generally use CFA to test whether the data match the existing models (Chan et al, 2022). If no model has been proposed, EFA can be used to explore the relationships between variables (model), and then CFA is employed to test and modify the model (Alotaibi & Alotaibi, 2021;Pereira et al, 2021).…”
Section: Knowledge Structure and Factor Analysismentioning
confidence: 99%